New Estimates of Public Employment and Training Program Net Impacts: A Nonexperimental Evaluation of the Workforce Investment Act Program - Heinrich, Carolyn J.; Mueser, Peter R.; Troske, Kenneth R.; Jeon, Kyung-Seong; Kahvecioglu, Daver C. (My University, 2009)
Two federal job training programs for adults lead to higher wages in the long run. People with poor work histories who enrolled in training through the Workforce Investment Act's Adult Program initially had lower wages, but after 10 quarters they caught up with people who did not receive training. Participants in the Dislocated Worker Program also improved their wages in contrast to their comparison group over time. People in both programs had depressed wages during and immediately after the training period.